2017
DOI: 10.21079/11681/22734
|View full text |Cite
|
Sign up to set email alerts
|

An optimized combined wave and current bottom boundary layer model for arbitrary bed roughness

Abstract: The U.S. Army Engineer Research and Development Center (ERDC) solves the nation's toughest engineering and environmental challenges. ERDC develops innovative solutions in civil and military engineering, geospatial sciences, water resources, and environmental sciences for the Army, the Department of Defense, civilian agencies, and our nation's public good. Find out more at www.erdc.usace.army.mil. To search for other technical reports published by ERDC, visit the ERDC online library at http://acwc.sdp.sirsi.net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…For comparison, we fit our simulation results to the wave and current boundary layer model developed by Styles et al (), which is a variant of the model of Grant and Madsen () in that Styles et al () assume a three‐layer rather than two‐layer eddy viscosity model. The model of Styles et al () is employed in the commonly used Regional Ocean Modeling System (Warner et al, ) to specify the bottom stress in combined wave and current conditions. The model requires a mean velocity specified at a reference height, which we assume is z = H /4, a median grain or floc diameter for the sediment bed, a bottom orbital velocity, a wave semiexcursion length, and the angle between the waves and currents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, we fit our simulation results to the wave and current boundary layer model developed by Styles et al (), which is a variant of the model of Grant and Madsen () in that Styles et al () assume a three‐layer rather than two‐layer eddy viscosity model. The model of Styles et al () is employed in the commonly used Regional Ocean Modeling System (Warner et al, ) to specify the bottom stress in combined wave and current conditions. The model requires a mean velocity specified at a reference height, which we assume is z = H /4, a median grain or floc diameter for the sediment bed, a bottom orbital velocity, a wave semiexcursion length, and the angle between the waves and currents.…”
Section: Resultsmentioning
confidence: 99%
“…Various extensions (e.g., Glenn & Grant, ; Styles & Glenn, ) of this model have been proposed that also include the effects of sediment‐induced stratification. Although these models and many others (Christoffersen & Jonsson, ; Styles et al, ) provide rich information about wave, current, and sediment interactions, they often assume a fully turbulent wave boundary layer with mixing represented by a time‐invariant eddy viscosity and that the sediment bed is hydraulically rough (e.g., Glenn & Grant, ; Grant & Madsen, ; Styles et al, ). Although these assumptions are valid for high Reynolds number waves over sandy bottoms, they do not always apply to estuarine conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, no wave‐current boundary layer model that we are aware of directly accounts for the wave momentum flux. Rather, most parameterize the effect of waves through a combined wave‐current friction velocity, which itself defines a logarithmic velocity profile inside the wave boundary layer (Grant & Madsen, ; Styles et al, ; Styles & Glenn, ). The velocity profiles that we measured were not logarithmic inside the wave boundary layer, and we found that the wave momentum flux was often the dominant component of the total bed shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous models to describe the combined wave‐current bed shear stress have been proposed over the years, and many imply that wave‐current interactions increase the “apparent” bottom roughness and induce additional drag on the flow (Grant & Madsen, ; Styles et al, ; Styles & Glenn, ; You et al, ). However, one recent numerical study suggests that the opposite effect may be seen in estuarine environments with smooth beds; that is, the drag decreases with the addition of laminar waves (Nelson & Fringer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the field programs over the past two decades used benthic landers and tripods equipped with a suite of optical and acoustic sensors at a single location to understand sediment resuspension and transport dynamics [ Trowbridge and Nowell , ; Agrawal and Pottsmith , ; Harris et al ., ; Styles and Glenn , ]. These sensor platforms have provided a wealth of information that have aided in the development of one‐dimensional bottom boundary layer models (BBLMs) that take into account combined wave and current interactions [ Grant and Madsen , ; Glenn and Grant , ; Madsen and Wikramanayake , ; Madsen , ; Styles and Glenn , ; Warner et al ., ]. These one‐dimensional models generally require input of wave and current data and a significant amount of tuning in order to accurately predict sediment resuspension and transport at a specific location.…”
Section: Introductionmentioning
confidence: 99%